Interception of telecommunications transport networks as a means of obtaining evidence operational units. - Іскендеров, Е.Ф (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2016)
The paper highlights the issues of obtaining evidence by operational units by interception of telecommunications transport networks. Specifies by author, that the current Criminal Procedure Code of Ukraine in p. 4 of Art. 263 does not include among the subjects interception of telecommunications transport networks operational and technical departments National Anti-Corruption Bureau of Ukraine. In this connection, the National Anti-Corruption Bureau of Ukraine detectives for take an evidence of signs to their jurisdictional crimes draw on written assignments relevant operational and operational-technical units for interception of telecommunications transport networks. This procedural order interception of telecommunications traffic is not entirely logical, as often subjects of commit are employees of the preliminary investigation, including of the National Police or Security Service of Ukraine. Accordingly, operational and technical units of the National Police or Security Service of Ukraine, performing assignments detectives of National Anti-Corruption Bureau of Ukraine, advance can prevent the persons concerned of the fact that the use of appropriate means of obtaining evidence. So, author talk about the risk of information leakage. Therefore stipulating the possibility of operating units of National Anti-Corruption Bureau of Ukraine carry out interception of telecommunications transport networks.It is noted that procedural order to obtain evidence through the interception of telecommunications transport networks are not entirely logical and not comply with the legal principles of criminal procedure proof. In this connection author proposes to change Art. 263 of CPC of Ukraine by complement p. 5 as follows:

У статті висвітлюються проблемні питання отримання доказів оперативними підрозділами шляхом зняття інформації з транспортних телекомунікаційних мереж. Запропоновано науково-обґрунтовані пропозиції щодо їх вирішення.
ЗНЯТТЯ ІНФОРМАЦІЇ З ТРАНСПОРТНИХ ТЕЛЕКОМУНІКАЦІЙНИХ МЕРЕЖ ЯК ЗАСІБ ОТРИМАННЯ ДОКАЗІВ ОПЕРАТИВНИМИ ПІДРОЗДІЛАМИ
Keywords: proving; interception of telecommunications transport network; operational units; covert investigative (detective) actions; evidence; доказування; зняття інформації з транспортних телекомунікаційних мереж; оперативні підрозділи; негласні слідчі (розшукові) дії; доказ